2016
DOI: 10.1007/s12011-016-0883-0
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Combined Effects of Arsenic and Lead on Behavioral and Biochemical Changes in Mice

Abstract: Arsenic (As) toxicity has caused an environmental tragedy affecting millions of people in the world. Little is known about the toxic effects of As on neurobehavioral and biochemical changes in vivo. Along this line of metal toxicity, co-exposure of lead (Pb) could aggravate the situation in the host. The present study was designed to explore the combined effects of As and Pb on behavioral changes like anxiety, spatial memory and learning impairment, and blood indices related to organ dysfunction. Exposure of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 57 publications
0
19
1
Order By: Relevance
“…As-induced changes in NOR have been previously reported (Martinez-Finley et al, 2009a), although it is not indicated whether these effects differed by sex. In contrast to our findings with elevated plus maze in which As increased the time spent in the open arms and thus could be considered ‘anxiogenic’, others have reported anxietylike phenotypes (Aktar et al, 2017; Chang et al, 2015), whereas in another study, anxiety and anti-anxiogenic effects were observed depending upon As exposure level (Umezu et al, 2012). Taken together, our work indicates that prenatal stress can modulate the developmental neurotoxicity of multiple metals including Pb, MeHg, and now As (Cory-Slechta et al, 2010; Cory-Slechta et al, 2004; Rossi-George et al, 2009; Rossi-George et al, 2011; Weston et al, 2014a; Weston et al, 2014b).…”
Section: Discussioncontrasting
confidence: 99%
“…As-induced changes in NOR have been previously reported (Martinez-Finley et al, 2009a), although it is not indicated whether these effects differed by sex. In contrast to our findings with elevated plus maze in which As increased the time spent in the open arms and thus could be considered ‘anxiogenic’, others have reported anxietylike phenotypes (Aktar et al, 2017; Chang et al, 2015), whereas in another study, anxiety and anti-anxiogenic effects were observed depending upon As exposure level (Umezu et al, 2012). Taken together, our work indicates that prenatal stress can modulate the developmental neurotoxicity of multiple metals including Pb, MeHg, and now As (Cory-Slechta et al, 2010; Cory-Slechta et al, 2004; Rossi-George et al, 2009; Rossi-George et al, 2011; Weston et al, 2014a; Weston et al, 2014b).…”
Section: Discussioncontrasting
confidence: 99%
“…Interactions among stressors are commonly classified as antagonistic (when the effect of one stressor reduces the effect of the other one), additive (when stressors have cumulative effects) or synergistic (when stressors together have a greater effect than the sum of their individual effects) (Folt et al, 1999). Additive effects of As, Cu and Pb have been described for humans (Lin et al, 2016), rats (Aktar et al, 2017;Mahaffey et al, 1981;Schmolke et al, 1992) and fishes (Verriopoulos and Dimas, 1988). In rats, for instance, co-exposure to Pb and As disrupted brain biogenic amine levels (Agrawal et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…ROS are the main participants in damage caused by neurodegenerative processes, including cell death [52,53]. Following this, the ROS production triggered by As accumulation in mice brains has been associated with neurobehavioral changes, mainly anxiety and depression [54,55]. Moreover, we detected degenerative changes in cerebral cortex neurons, such as those reported by Selim et al [56] and alterations in behavior from the first days of exposure that was characterized by a marked aggressiveness in group IV (the mice fed with drinking water containing the highest concentration of As of the three sources sampled).…”
Section: Discussionmentioning
confidence: 99%